Blue Economy Literacy Framework for Coastal Communities: Integrating Marine Conservation, Maritime Entrepreneurship, and Cultural Heritage - Barasa, Larsen; Aditya Rinaldi; Aji Permana; M. Anang Jatmiko; Ikhwanuddin (Marasofi International Media and Publishing (MIMP), 2026)
Coastal communities worldwide face unprecedented livelihood threats as 680 million inhabitants experience declining fish stocks, climate change impacts, and economic marginalization despite residing adjacent to valuable marine resources. This research develops a comprehensive Blue Economy Literacy Framework integrating marine conservation education, maritime entrepreneurship training, and cultural heritage preservation to enable sustainable coastal socio-economic development. Through qualitative analysis incorporating perspectives from marine biologists, community development specialists, and coastal education practitioners, this study identifies critical curriculum components, pedagogical approaches, and implementation barriers constraining coastal capacity building initiatives. The framework synthesizes marine biology, social sciences, economics, and educational pedagogy, demonstrating how multidisciplinary literacy programs can simultaneously enhance environmental stewardship, economic opportunity creation, and cultural identity preservation while addressing power asymmetries and gender inequities prevalent in coastal societies. Findings reveal significant gaps in current coastal education approaches, particularly regarding integration of traditional ecological knowledge with scientific marine conservation principles and connection of environmental protection with livelihood generation strategies. The research contributes actionable implementation pathways for coastal stakeholders globally, offering evidence-based strategies for transformative education aligned with SDG 14 (Life Below Water) and SDG 1 (No Poverty), while empowering marginalized coastal populations through knowledge, skills, and agency essential for sustainable coastal futures.